Provisions for Effective Development of Regional Agricultural Systems in Russia’s Economy - KUZNETSOV, Nikolai Ivanovich; UKOLOVA, Nadezhda Viktorovna; MONAKHOV, Sergey Vladimirovich; SHIKHANOVA, Juliya Anatolyevna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
Modern methodical approaches to the formation and development of highly efficient regional agricultural economies are being analyzed. On the basis of the prevailing conditions of agricultural production, priority areas for improving the production process and the regulation of regional agricultural economies are being identified. The example of the Saratov region shows the experience of making the region a leader in the agrarian sector of Russia’s economy. The scheme of interaction between economic entities of the region within the framework of the existing agricultural cluster is being presented. The authors come to the conclusion that the effective development of regional agricultural economy is impossible without the creation of a good social and productive infrastructure, as well as a solid scientific base, and the introduction of new production technologies.